2009
DOI: 10.1186/1471-2148-9-202
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and functional divergence of NLRPgenes in mammalian reproductive systems

Abstract: BackgroundNLRPs (Nucleotide-binding oligomerization domain, Leucine rich Repeat and Pyrin domain containing Proteins) are members of NLR (Nod-like receptors) protein family. Recent researches have shown that NLRP genes play important roles in both mammalian innate immune system and reproductive system. Several of NLRP genes were shown to be specifically expressed in the oocyte in mammals. The aim of the present work was to study how these genes evolved and diverged after their duplication, as well as whether n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 80 publications
5
115
0
2
Order By: Relevance
“…Our finding that Cyp2a(4/5)bgs-null mice are viable and fertile indicates that these five non-Cyp genes are not critical for embryonic or postnatal development or for reproduction. The Nalp4 and Nalp9 (also named Nlrp4 and Nlrp9) genes are members of the NLRP (nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain-containing proteins) gene family (Tian et al, 2009), which are mainly expressed in oocytes and embryos in early developmental stages. The availability of the Cyp2a(4/5)bgs-null mouse, as a Nlrp9c-4a-9a knockout mouse, may be helpful for studies on potential compensatory mechanisms in the oocyte, and on other potential biologic functions of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that Cyp2a(4/5)bgs-null mice are viable and fertile indicates that these five non-Cyp genes are not critical for embryonic or postnatal development or for reproduction. The Nalp4 and Nalp9 (also named Nlrp4 and Nlrp9) genes are members of the NLRP (nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain-containing proteins) gene family (Tian et al, 2009), which are mainly expressed in oocytes and embryos in early developmental stages. The availability of the Cyp2a(4/5)bgs-null mouse, as a Nlrp9c-4a-9a knockout mouse, may be helpful for studies on potential compensatory mechanisms in the oocyte, and on other potential biologic functions of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Genes in this group included DCD-an antimicrobial peptide coding gene, member of the APOBEC family which are specific to primates and mammals [54]. Furthermore, nLRP11 -a member of the Nod-like receptor protein family was observed to be present only in mammals [55]. Analysis of the variations in the extent of conservation between classical and nonclassical RBPs across species showed that there is no significant difference (p=0.1, Fishers exact test)( Figure 3E).…”
Section: Rbps Are Highly Conserved Across Speciesmentioning
confidence: 98%
“…Because three Nlrp genes show lineage-specific duplications including Nlrp1 (Nlrp1a, Nlrp1b and Nlrp1c), Nlrp4 (Nlrp4a-Nlrp4g) and Nlrp9 (Nlrp9a, Nlrp9b and Nlrp9c), meanwhile, Nlrp7, Nlrp8, Nlrp11 and Nlrp13 are lost in the mouse. The phylogenetic analyses identified a well supported reproduction-related clade including nine NLRP proteins (NLRP2,4,5,7,8,9,11,13 and 14) in humans (Tian et al 2009). In the reproduction-related NLRP cluster, there are several oocyte-specific NLRP genes including NLRP2, 4, 5, 8, 9 and 14 (Tian et al 2009).…”
Section: Discussionmentioning
confidence: 92%
“…The phylogenetic analyses identified a well supported reproduction-related clade including nine NLRP proteins (NLRP2,4,5,7,8,9,11,13 and 14) in humans (Tian et al 2009). In the reproduction-related NLRP cluster, there are several oocyte-specific NLRP genes including NLRP2, 4, 5, 8, 9 and 14 (Tian et al 2009). …”
Section: Discussionmentioning
confidence: 92%